A Comparison of English and Arabic Noun Inflectional Morphology - MEDJEDOUB , Rima (Journal of Human Sciences, 2022)
The present study explores the inflectional systems of Arabic and English nouns with special attention to the similarities and differences between them. In other terms, this paper aims to answer the following research questions: What forms are used to mark the Arabic and English nouns for inflection? To which extent is inflection in Arabic nouns identical to/varied from that in English nouns? To do so, it is essential to describe the inflectional morphology of nouns in each language and explain how they are inflected and for which category/ies. A systematic comparison, then, is carried out between the two morphological systems. The outcome of the study reveals that the English nouns are weakly inflected as opposed to the Arabic ones. It is noteworthy that the results of this study are majorly applicable in the fields of second language learning, translation and machine translation.